Model of integrating service learning in the teaching of disaster readiness and risk reduction (DRRR): Focus on physics - Catindig, Jhoanne (Animo Repository, 2021)
The study focused on the development of a model on integrating service learning in the teaching of disaster readiness and risk reduction, focused on physics. Students’ previous physics lessons were integrated to current DRRR topics through selected YouTube videos. Students used their brochures to discuss and describe the nature, cause and possible preventions from the dangers caused by different disasters to the community participants. Both quantitative data, in the form of survey on disaster related knowledge, civic action skills and attitude toward disaster were gathered from the students and community participants, and qualitative data, in the form of reflections, narratives, and interviews for the students and short response from the community. Similarly, the survey instruments and evaluation form were translated to Filipino language to avoid context confusion from the community participants. Results showed that both the students and the community participants agreed that the integration of physics in DRRR lessons have helped them further understand the discussions. Similarly, the students perceived that the service learning activity has helped them improve their communication and social skills, and leadership skills for the community participants. Additionally, both participants agreed that the service learning activity served as an instrument in accommodating individual differences and solving community problems during disaster. Lastly, the model of integrating service learning in the teaching of disaster readiness and risk reduction focused on physics was validated by selected DRRR and physics teachers and was proven to be useful in teaching DRRR and integrating physics and other related subjects.